(untitled) (Education in the 21st Century, 2023)
Since the independence of the Republic of Armenia, there has been a need to shake off the 70-year-old atheism of Soviet Armenia and create preconditions for the revival of the Christian faith. His Holiness Garegin I, Supreme Patriarch of all Armenians, was one of the prominent figures of that period, decisive for the Armenian people of the 20th century, who undertook the difficult and responsible mission of reviving our people’s moral health and sowing rapprochement with their own identity. In his sermons and works, philosophical concepts and their religious interpretations, His Holiness presents the issues of self-knowledge in a new light. Identity, self-description, great sincerity and courage are needed to reveal oneself. Especially when one has a tendency to self-justify. When making an effort for self-knowledge, one must be able to overcome that psychology, otherwise it will close the person’s "self-consciousness" like an opaque curtain. Knowledge of the truth is necessary to live the truth in practical life to find true ways. Its people don’t know what is good, evil, justice, honesty and beauty, then they cannot find the secret to a happy life. A question arises: aren’t philosophy, based on its intellect, and religion, based on its belief, contradictory concepts? After all, many theologians and philosophers have different points of view on these issues. According to His Holiness, the intellect cannot be an obstacle to faith; on the contrary, it is a powerful element in the manifestation of the faith in life. Faith reveals to us the God who is in direct contact with us, but not the God who is the order of thought and concerned only to the intellect. 225 With this reasoning and logic, ethics can be considered as the basis of religion. But in that case, what’s the difference between religion and philosophy (ethics), if both are based on faith and love for God, humanity and self-sacrifice? According to His Holiness’s observations, we come to the clear conclusion that knowing oneself, "Know yourself", is always imperative for a person. Philosophy on the basis of reason and religion on the basis of faith are not contradictory.